2004
DOI: 10.1186/2046-0481-57-5-289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liner design, pulsator setting, and vacuum level on bovine teat tissue changes and milking characteristics as measured by ultrasonography

Abstract: Friesian-type dairy cows were milked with different machine settings to determine the effect of these settings on teat tissue reaction and on milking characteristics. Three teat-cup liner designs were used with varying upper barrel dimensions (wide-bore WB = 31.6 mm; narrow-bore NB = 21.0 mm; narrow-bore NB1 = 25.0 mm). These liners were tested with alternate and simultaneous pulsation patterns, pulsator ratios (60:40 and 67:33) and three system vacuum levels (40, 44 and 50 kPa). Teat tissue was measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 6 publications
5
58
0
Order By: Relevance
“…Phenotypic correlations between milk fractions, teat end wall thickness and vacuum for opening the teat sphincter in goats of the indigenous Greek breed gested that these findings depended on the characteristics of used materials and proved that the modifications in TEWT depended on the diameter of the liner as well as on its stiffness. Gleeson et al (2004) also stated that the liner design appeared to have a bigger effect on the teat tissue changes than pulsation characteristics or vacuum level. In cows Hamann and Mein (1996a) recommended that the teat thickness changes after milking should be lower than +5% in order to prevent excessive teat oedema and greater than -5% in order to limit an excessive compression load of the liner over the teat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic correlations between milk fractions, teat end wall thickness and vacuum for opening the teat sphincter in goats of the indigenous Greek breed gested that these findings depended on the characteristics of used materials and proved that the modifications in TEWT depended on the diameter of the liner as well as on its stiffness. Gleeson et al (2004) also stated that the liner design appeared to have a bigger effect on the teat tissue changes than pulsation characteristics or vacuum level. In cows Hamann and Mein (1996a) recommended that the teat thickness changes after milking should be lower than +5% in order to prevent excessive teat oedema and greater than -5% in order to limit an excessive compression load of the liner over the teat.…”
Section: Discussionmentioning
confidence: 99%
“…In cows, an increase in the teat end wall thickness (TEWT) was observed after milking (Hamann and Mein, 1990). Gleeson et al (2004) found in cows that vacuum levels of 50 and 40 kPa gave similar changes in the teat tissue after machine milking. In contrast Le Du and Taverna (1989) observed a reduction in TEWT after milking.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, the teats may become more sensitive for the entry of pathogens with intramammary infections as a result. Therefore, the condition of the teat plays a considerable role in the incidence of mastitis infections (Bhutto, Murray, Woldehiwet, 2010;Gleeson, O'Callaghan, Rath, 2004). Besides the greater risk on penetration of bacteria into the udder, these changes in teat condition are generally accompanied by discomfort and pain, which negatively influence the milking process.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the greater risk on penetration of bacteria into the udder, these changes in teat condition are generally accompanied by discomfort and pain, which negatively influence the milking process. The design of the teatcup liner has a larger effect on teat tissue changes than other machine settings (Gleeson et al, 2004). In addition, the liner design has proven to have a great influence on milking characteristics (Mein, Reinemann, O'Callaghan, Ohnstad, 2003).…”
Section: Introductionmentioning
confidence: 99%